Pengaruh Kepemimpinan Dan Stres Kerja Terhadap Kinerja Karyawan Star ABC - Nanda Hanifah Putri; Sugeng Suroso; Ery Teguh Prasetyo (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the influence of leadership and work stress on the performance of STAR ABC employees. The research method used is quantitative research, where this research is used to examine certain populations and samples, data collection uses research instruments, quantitative or statistical data analysis, aims to test predetermined hypotheses. The sampling technique used is a saturated sampling technique or the entire population is sampled. The population in this study was 55 respondents. Data analysis uses Smart PLS 4 software and hypothesis testing, namely the t test and F test. Based on the results of the path coefficient hypothesis test, there are P-values ​​of 0.000 or <0.05 and the leadership t-statistics value is 4,089 or > 1.96. So it is stated that there is a significant influence between leadership variables on employee performance. And based on the results of the path coefficient hypothesis test, there is a P-value of 0.419 or <0.05 and the work stress t-statistics value is 0.808 or >1.96, so it is stated that there is no significant influence between the work stress variable on employee performance.